Pengaruh Aromaterapi Peppermint terhadap Emesis Gravidarum pada Ibu Hamil Trimester Pertama: Studi One-Group Pretest–Posttest - Deka Nona Novita; Asep Kuswandi; Tetik Nurhayati; Dewi Ariyanti (STIKes Persada Husada Indonesia, 2026)
Research Objective: This study aimed to examine changes in the severity of emesis gravidarum before and after inhaled peppermint aromatherapy among first-trimester pregnant women in the working area of the Purbaratu Public Health Center, Tasikmalaya City. Methodology: A pre-experimental one-group pretest–posttest design was used. Twenty participants with complete paired data were analyzed. Emesis gravidarum severity was measured using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE-24) questionnaire before and after inhalation of two to three drops of peppermint essential oil administered once daily for three consecutive days. Paired Sample t-test analysis was used after the normality assumption was met. Results: The mean PUQE-24 score decreased from 9.50 (SD = 1.235) before the intervention to 3.30 (SD = 1.128) after the intervention, with a mean reduction of 6.20 points (p < 0.001). Conclusion: In this small uncontrolled study, inhaled peppermint aromatherapy was associated with a significant reduction in emesis gravidarum scores. The findings provide preliminary support for its use as a complementary approach, but controlled studies and continued maternal safety monitoring are required before routine implementation.